2019
DOI: 10.1155/2019/1325181
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Balanced Innate Lymphoid Cell Subsets in Intestinal Homeostasis, Chronic Inflammation, and Cancer

Abstract: Innate lymphoid cells (ILCs) comprise a recently identified subset of innate immune cells that are mainly localized to mucosa-associated tissues. Although they have not yet been fully characterized, they can generally be divided into ILC1s, ILC2s, and ILC3s. ILCs and their corresponding cytokines act as important mediators of the early stages of the immune response during inflammation, tissue repair, and the maintenance of epithelial integrity. Consequently, the dysregulation of ILC subsets might promote infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 121 publications
(143 reference statements)
2
5
0
Order By: Relevance
“…RNA-Seq showed that among the DEGs in tumour versus distal ILC3s, many were associated with tumour development or inhibition (Table S3); however, most of the DEGs were involved in tumour suppression, especially SCIN, which was upregulated in tumour ILC3s. These data concur with previous studies suggesting that ILC3s in the tumour microenvironment might have dual functions depending on the cancer phase and environmental context [20,[36][37][38].…”
Section: Discussionsupporting
confidence: 92%
“…RNA-Seq showed that among the DEGs in tumour versus distal ILC3s, many were associated with tumour development or inhibition (Table S3); however, most of the DEGs were involved in tumour suppression, especially SCIN, which was upregulated in tumour ILC3s. These data concur with previous studies suggesting that ILC3s in the tumour microenvironment might have dual functions depending on the cancer phase and environmental context [20,[36][37][38].…”
Section: Discussionsupporting
confidence: 92%
“…RNA-Seq showed that among the DEGs in tumor versus distal ILC3s, many were associated with tumor development or inhibition ( Figure 3 ); however, most of the DEGs were involved in tumor suppression, especially SCIN , which was upregulated in tumor ILC3s. These data concur with previous studies suggesting that ILC3s in the tumor microenvironment might have dual functions depending on the cancer phase and environmental context ( 20 , 36 38 ).…”
Section: Discussionsupporting
confidence: 93%
“…ILCs play an important role in maintaining barrier homeostasis, blocking bacterial and viral infections, expelling parasites, tissue repair, and tumor immunity. ILCs are dysregulated in multiple human diseases [ 37 ], including allergic inflammation and asthma [ 17 22 ], and IBD [ 23 25 ]. The main ILC population involved in airway inflammation appears to be ILC2 [ 17 22 ], while ILC3 appears to be the population the most involved in IBD [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%